Respuesta :
2p + q = 1
9p + 3q + 3 = 0
q = 1 - 2p
replace q = 1 - 2p into 9p + 3q + 3 = 0
9p + 3(1 - 2p) + 3 = 0
9p + 3 - 6p + 3 = 0
3p + 6 =0
3p = -6
p = -2
q = 1 - 2p
q = 1 -2(-2)
q = 1 + 4
q = 5
(-2 , 5)
answer
{(-2, 5)} first one
9p + 3q + 3 = 0
q = 1 - 2p
replace q = 1 - 2p into 9p + 3q + 3 = 0
9p + 3(1 - 2p) + 3 = 0
9p + 3 - 6p + 3 = 0
3p + 6 =0
3p = -6
p = -2
q = 1 - 2p
q = 1 -2(-2)
q = 1 + 4
q = 5
(-2 , 5)
answer
{(-2, 5)} first one
Answer:
Solution set is {-2,5}
First option is correct!
Step-by-step explanation:
2p+q = 1 ,solving the equation for q
q = 1-2p ..... equation (1)
9p+3q+3=0,dividing the equation by 3
3p+q+1=0, using substituting method
3p+(1-2p)+1=0
3p-2p+2 =0
p +2 =0
p=-2
substituting the value of p in q=1-2p ,we get
q = 1-2(-2) = 1+4 =5
solving it for p and q ,we get (-2,5) solution set is {(-2,5)}